Evolução de um sistema lacustre árido Permiano, parte superior da Formação Pedra de Fogo, borda oeste da Bacia do Parnaíba - ANDRADE, Luiz Saturnino de (2015)
Stratigraphic and facies analysis in the Filadélfia region, TO, BR, at the western of the Parnaíba Basin, allowed redefine the paleoenvironment of the upper portion of the Pedra de Fogo Formation of Permian age. The studied deposits are a series of approximately 100 m thick, predominantly siliciclastic, with subordinate carbonates and evaporites, where were defined 21 sedimentary facies that could be grouped into six facies associations (AF): AF1) Lacustrine with ephemeral river deposits; AF2) Storm wave-influenced lake deposits; AF3) Continental sabkha deposits; AF4) Central lake deposits; AF5) Eolian dunes field deposits; and AF6) Lake/oasis deposits with inunditos. These associations indicate that during Permian, an extensive lacustrine arid system developed adjacent to eolian dunes fields and continental sabkha, as well as with contributions from ephemeral rivers. Fluvial incursions into lakes propitiated the formation of suspension lobes and sheet flows (AF1). Sabkha plains (AF3) were formed in the marginal portions of the lake that eventually were influenced by storms waves (AF2), while central zone were site of intense pelitic deposition (AF4). The low supply of eolian sand in this system resulted in the formation of restricted dune fields (AF5), with development of interdune lakes (oasis), where proliferating giant ferns, sporadically flooded by ephemeral rivers (AF6). The facies associations data, corroborated by the paleogeography of the region during the Late Permian, indicate that settling of the top part of the Pedra de Fogo Formation was laid during a hot and arid climate.